2016
DOI: 10.1002/chem.201601494
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Turbo‐Hauser Base TMPMgCl⋅LiCl in [D8]THF

Abstract: What is the most significant result of this study? The most comprehensive three dimensional structural information we currently can have from molecules stem from X-ray diffraction of the solid state. We need to have this information because we have to identify reactive species which might have to be modified to further foster their chemical performance. Turbo-Hauser bases are such outstanding performers, as they show enhanced reactivity while being gentle to many other present functional groups at the same tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Without base, only as mall amount of the desired product 2a is formed (entry 1). Unlike the TMP-derived Hauser base 4a (entry 2), the presence of the DIPA-derivative 4b [15b] has ap ositive effect under these restrictive conditions,b ut cannot produce satisfactory yields of 2a.I nspired by the recent studies on Knochel-Hauser bases [17] (and in stark contrast to 4b), to our surprise we found that the rare DIPAMgCl·LiCl (4d) [18] promoted the formation of 2a in 91 %y ield (entry 5). [17b, 18] Thesynergy between an optimal Li/Mg ratio (entries 6and 7; see Tables S1 and S2 in the Supporting Information) and the specific diisopropylamide base (entries 4a nd 5) are both critical at enabling this reaction.…”
mentioning
confidence: 52%
“…Without base, only as mall amount of the desired product 2a is formed (entry 1). Unlike the TMP-derived Hauser base 4a (entry 2), the presence of the DIPA-derivative 4b [15b] has ap ositive effect under these restrictive conditions,b ut cannot produce satisfactory yields of 2a.I nspired by the recent studies on Knochel-Hauser bases [17] (and in stark contrast to 4b), to our surprise we found that the rare DIPAMgCl·LiCl (4d) [18] promoted the formation of 2a in 91 %y ield (entry 5). [17b, 18] Thesynergy between an optimal Li/Mg ratio (entries 6and 7; see Tables S1 and S2 in the Supporting Information) and the specific diisopropylamide base (entries 4a nd 5) are both critical at enabling this reaction.…”
mentioning
confidence: 52%
“…The other experimental methods suggested that a more complicated series of equilibria were actually occurring in solution [210]. Similar studies were conducted on other mixed metal complexes, such as the Hauser bases, iPr 2 NMgCl [211] and TMPMgCl [212] and their turbo-derivatives, revealing that the Schlenk equilibrium can be replaced by a more complicated series of equilibria between different aggregations states and identifying the effect of more hindered amides [213] on the solution phase structures. Other alkaline earth metal species characterised by diffusion NMR methods and external calibration calculations include s-block bimetallic catalysts containing two magnesium atoms, stabilised by differing amounts of Na(THF) 3 depending on the solvent used [214], and multinuclear complexes of calcium-and containing π ligands [215].…”
Section: External Calibration -Examples and Applicationsmentioning
confidence: 75%
“…1 H, 29 Si and 13 C{ 1 H} NMR spectra were recorded on Bruker Avance III 400 (BBO, BBFO probes), Avance III HD 500 (BBO Prodigy probe) or Avance III HD 600 (TCI cryo probe) spectrometers. Chemical shifts are reported in parts per million relatively to SiMe 4 ( 1 H, 13 C) as an external standard referenced to the solvents residual proton signal using xiref AU program for 7 Li-NMR spectra. DOSY-NMR spectra were measured using the ledbpgp2 s standard pulse sequence.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Expectedly, equilibria between diverse species have been observed in solution by DOSY-NMR spectroscopy. [5,7] The preparation of these turbo-Hauser bases proceeds smoothly by deprotonation of secondary amines with Grignard reagents in the presence of lithium halide or with turbo-Grignard reagents such as iPrMgCl • LiCl. [8] Besides the widely used application of Hauser and turbo-Hauser bases as selective metalation reagents, we are interested in magnesium batteries.…”
Section: Introductionmentioning
confidence: 99%